NeuroSim Simulator for Compute-in-Memory Hardware Accelerator: Validation and Benchmark - Lu, Anni; Peng, Xiaochen; Li, Wantong; Jiang, Hongwu; Yu, Shimeng (Frontiers in Artificial Intelligence, 2021)
Compute-in-memory (CIM) is an attractive solution to process the extensive workloads of multiply-and-accumulate (MAC) operations in deep neural network (DNN) hardware accelerators. A simulator with options of various mainstream and emerging memory technologies, architectures and networks can be a great convenience for fast early-stage design space exploration of CIM hardware accelerators. DNN+NeuroSim is an integrated benchmark framework supporting flexible and hierarchical CIM array design options from device-level, to circuit-level and up to algorithm-level. In this paper, we validate and calibrate the prediction of NeuroSim against a 40nm RRAM-based CIM macro post-layout simulations. First, the parameters of memory device and CMOS transistor are exacted from the foundry’s process-design-kit (PDK) and employed on the NeuroSim settings; the peripheral modules and operating dataflow are also configured to be the same as the actual chip implementation. Next, the area, critical path and energy consumption values from the SPICE simulations at the module-level are compared with those from NeuroSim. Some adjustment factors are introduced to account for transistor sizing and wiring area in the layout, gate switching activity and post-layout performance drop, etc. We show that the prediction from NeuroSim is precise with chip-level error under 2% after the calibration. Finally, the system level performance benchmark is conducted with various device technologies and compared with the results before the validation. The general conclusions stay the same after the validation but the performance degrades slightly due to the post-layout calibration.